HOW TO HEDGE METALS a complete guide to hedging for companies that produce, consume, and trade physical metals. - Campbell, Lesley ([S.l.] : PRODUCTIVITY PRESS, 2024)
How to Hedge Metals is an important resource for all traders, whether new graduates or seasoned directors, and is written in simple, precise, and clear terms. It is engaging and accessible - a good read rather than a reference book - and provides solutions to the problems caused by metal price volatility. It walks through the entire hedging process, starting long before the first futures trade, with a discussion on risk tolerance and appetite. It explains how the world's major futures exchanges work; but more importantly, it explains how futures and options can solve physical trading problems. Written entirely from a hedger's perspective, How to Hedge Metals answers questions on issues such as Quotational Periods, option premiums, and backwardations. The aim of the book is not to promote hedging; some companies will learn how to minimise risk by changing their physical contracts, while others may conclude that the level of risk they face is acceptable. For those who decide to hedge there is a step-by-step guide to preparation, implementation, and evaluation of a hedging strategy, as well as case studies to illustrate how strategies have gone wrong in the past. Whatever their business model and knowledge of commodity markets, metal producers, fabricators and traders will understand what they can realistically achieve with a hedging program, and how to achieve it. This book deals with real world problems - contracts that are not in convenient 25 tons multiples, customers, and suppliers who change their minds, shipments that are delayed and markets that inexplicably move in ways that seem to defy the laws of supply and demand. Written by a respected industry expert who has worked for trading companies, banks, brokers, and the London Metal Exchange (LME), it uses simple language and engaging graphics to show how futures and options can offer protection from the increasing volatility of metal prices.
Keywords: Hedging (Finance); Metal trade; BUSINESS & ECONOMICS / Industries / Manufacturing Industries